Investigation of Circulating Extracellular Vesicle MicroRNA Following Two Consecutive Bouts of Muscle-Damaging Exercise - Lovett, Jason A. C.; Durcan, Peter J.; Myburgh, Kathryn H. (Frontiers in Physiology, 2018)
Background: Extracellular vesicles (EVs) are nano-sized vesicles that are known to be powerful mediators of intercellular communication via their microRNA (miR) content. A paucity of information on EV-mediated communication arising from skeletal muscle (SkM) in response to exercise-induced muscle damage is present in the published literature. Lack of such information inhibits our understanding of muscle injury and repair processes. Aims: To assess circulating EV levels and selected miR content within them, in response to two consecutive bouts of muscle-damaging exercise. Methods: Serum creatine kinase activity (CK) and EVs were analysed from the blood of 9 healthy, untrained males at baseline, and at 2 and 24 hr post-exercise. The exercise regimen consisted of a combination of plyometric jumping and downhill running. Perceived muscle pain (PMP) was assessed on a scale from 1 to 10. Plasma EVs were isolated using size exclusion columns and visualised with transmission electron microscopy (TEM). EV size and number were quantified using nanoparticle tracking analysis (NTA). miR expression was quantified using qPCR, with normalisation to an exogenous control (cel-miR-39). Results: PMP and CK were significantly elevated post-exercise compared to baseline levels, providing indirect evidence for muscle damage. EV visualisation using TEM revealed an abundant and heterogeneously-sized pool of intact particles within the exosome size range (30-150nm). No significant change in mean EV size or number was seen over time. The SkM-specific miR-206 in EVs was found to be variable among participants and no significant change occurred in SkM-important miRs; 1, 133a, 133b, 486 and 499a. However, EV miR-31 decreased from baseline to 24 hr post-exercise (p = 0.027). Conclusion: Mild to moderate exercise-induced muscle damage altered the miR-31 profile of circulating EVs within the first 24 hrs post exercise, but not that of myomiRs in EVs. These data demonstrate that EVs carry selectively packaged cargo which can be affected by exercise. Future research into the total miR content of EVs in response to exercise-induced muscle damage may reveal other miRs responsive to this relatively mild perturbation. More time points post muscle-damaging exercise would provide a better understanding of the temporal EV myomiR response.